Ikke blot en lære, men en åndsretning - Steenbuch, Johannes Aakjær (Dansk Teologisk Tidsskrift, 2016)
Since the foundation of the first Danish Baptist congregation in 1839, Danish Baptists have held widely different theological opinions. It may be argued, however, that many Danish Baptists have subscribed to what may be called a “narrative personalism”. By this concept is meant a narrative conception of faith that sees personal history as being central. The “personal” should be distinguished from the purely subjective or individual, on the one hand, and the collective or general, on the other. Danish Baptist theologians such as the founding father, P.C. Mønster, P. Olsen and Kjell Kyrø-Rasmussen have in different ways expressed views that made the concrete relationships between persons of faith in the community of believers more fundamental than, e.g., written creeds and other dogmatic expressions of faith.